Right Frontotemporoccipital Focal Epilepsy with Behavioral and Emotional Problems - Natalia Dewi (Archives of The Medicine and Case Reports, 2020)
Miss AN, female, 17 years old, Muslim, Betawi ethnicity, graduated from elementaryschool, currently no longer in school. The first febrile seizure patient was four yearsold. Five to seven years old, patients with recurrent seizures without fever, diagnosedwith epilepsy and do not see a doctor regularly. At 14 years, the patient was raped, andsince then, the patient has had free sex with many different men. At the age of,16, thepatient had seizures up to five times an ay, and one seizure was approximately fiveminutes. The patient went to a neurologist and was regularly treated with valproic acidand carbamazepine. At the age of 17 years, the patient often got angry when teased andthreatened with knives or scissors, had free sex with many men and went to apsychiatrist. The patient has been treated five times in different mental hospitalsbecause he often runs away from home. Currently, the patient is being treated in thepsychiatric ward and is receiving 2 x 500 mg of valproic acid, 3 x 200 mg ofcarbamazepine, 2 x 0.5 mg of Clonazepam and 1 x 50 mg of sertraline. At the time oftreatment, the patient is known to be HIV positive and does not need ARV therapy.Patients also planned behavioural therapy and involved patients with activities atYayasan Pelita Ilmu. It is hoped that this therapy can help overcome the patient'sbehavioural and emotional problems.